2022
DOI: 10.3390/biomedicines10071744
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Obesity-Related Indices Are Associated with Rapid Renal Function Decline in a Large Taiwanese Population Follow-Up Study

Abstract: A rapid decline in renal function can cause many complications, and therefore it is important to detect associated risk factors. Few studies have evaluated the associations among obesity-related indices and metabolic syndrome (MetS) with renal function decline. This longitudinal study aimed to explore these relationships in a large cohort of Taiwanese participants. The studied obesity-related indices were waist-to-height ratio (WHtR), A body shape index (ABSI), visceral adiposity index (VAI), lipid accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
7
1
Order By: Relevance
“…Waist circumference, an index for abdominal obesity, was measured at the superior border of the iliac crests. BMI, WtHR, CI, ABSI, BRI and LAP were calculated according to previous published formulae ( 13 ) as followed:…”
Section: Methodsmentioning
confidence: 99%
“…Waist circumference, an index for abdominal obesity, was measured at the superior border of the iliac crests. BMI, WtHR, CI, ABSI, BRI and LAP were calculated according to previous published formulae ( 13 ) as followed:…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, neither WC nor BMI can be used as the best predictor of renal function in the US adult population. Previous studies have shown that WHtR is strongly associated with renal function [ 24 , 26 , 27 ]. Our study also showed that the prevalences of CKD and albuminuria increased 6-fold and 6.19-fold, respectively, for each unit increase in WHtR.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, WC was measured at the superior border of the iliac crests. The ABSI and BRI were calculated according to the previous published formulae [ 20 ] as follows: …”
Section: Methodsmentioning
confidence: 99%